Pengaruh Frekuensi Ibadah Harian terhadap Kebahagiaan Siswa Muslim SMP Al-Khairiyah Jakarta Utara - Faikha, Faikha; Zahidah, Najma (ALSYS, 2025)
Happiness is a vital aspect of adolescent life, particularly for junior high school students who are undergoing a transitional phase in psychological and social development. In Indonesian society, where the majority of the population is Muslim, daily religious practices serve not only as spiritual activities but also as integral components of a lifestyle that influences emotional well-being. This study aims to identify the effect of daily worship frequency on the happiness levels of Muslim students at SMP Al-Khairiyah, North Jakarta. A quantitative approach with a cross-sectional design was employed, involving 60 students selected through proportional stratified sampling. Data were collected using indicators of daily worship frequency and The Oxford Happiness Questionnaire (OHQ), and analyzed using simple linear regression. The results indicate that the frequency of daily worship contributes significantly to the happiness of Muslim students, accounting for 17.1% of the variance. These findings affirm that daily religious practice plays an important role in supporting the psychological well-being of Muslim adolescents. The implication is that schools should encourage and integrate worship habits within the educational environment as a strategy to enhance students’happiness and emotional balance.